Glacial Retreat Patterns and Processes on Antarctic Continental Margins - Prothro, Lindsay O'Neal (2018)
Antarctic ice margins are complex and dynamic, and Antarctic ice sheets hold a volume of ice equivalent to ~53 meters of sea level rise. The necessity of understanding ice margins and their stability motivates advances in ice-sheet and sea-level modeling, but models must be tested and tuned using observational data. However, contemporary ice margins are difficult to access and offer a limited spatial and temporal glimpse of the processes that occur where the ocean meets the ice. Therefore, geologic investigations of now-deglaciated portions of the Antarctic continental shelf are used to provide a more substantial record of the timing, rates, and patterns of past ice sheet retreat, as well as the mechanisms that have caused instability in the past. This study merges data from sediment cores, bathymetric mapping, and radiocarbon dating to provide records of ice-sheet retreat on Antarctic continental margins. Cores from the Ross Sea have been analyzed to develop a new sediment facies model that is reflective of geomorphic context. This facies model is designed to improve interpretations of events dated with radiocarbon. Analysis of sedimentary facies relative to seafloor geomorphology has also revealed a contrasting retreat style of the East Antarctic Ice Sheet (EAIS) from the West Antarctic Ice Sheet (WAIS) following the Last Glacial Maximum, with the EAIS retreating continuously and the WAIS remaining stable for long periods of time before episodically retreating over large distances. Previously-published and newly-acquired radiocarbon ages have been interpreted within the context of the updated facies model and have been found to reveal a highly complex EAIS retreat pattern that includes a major mid-Holocene ice shelf collapse, reorganization of drainage, and readvance of ice. Furthermore, these new results have mitigated previous discrepancies between marine and terrestrial records of ice sheet retreat. The sediment facies model has also been used to interpret previously-published and newly-acquired radiocarbon ...